Peranan Angka Latin Dalam Meningkatkan Hasil Belajar Bahasa Mandarin Pada Siswa Kelas XII Jurusan Bahasa SMA Santa Ursula Jakarta - Prajaniati Susanto; Tri Budianingsih; Sri Hartati (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
Mandarin is one of an international language that is increasingly widely used but has a high level of difficulty to learn. The existing Chinese teaching methods need to be added new methods to make it more interesting, one of them is by using the Latin numeral method which is widely used in social media. This experimental research was conducted by taking respondents with the same sex and age, to prove the relationship between the independent variable (Mandarin learning process) and the dependent variable (Latin numeral method). The similarity of sounds in Latin numbers and pronunciation of Chinese Han characters (Chinese Homonym) is proven to help respondents understand the meaning of Chinese sentences more than 80%, even 4 of the 9 questions presented showed a difference in the correct answers before and after the test by more than 29%. Similar sound similarities (homonyms) between the pronunciation of Chinese Han characters and the pronunciation of numbers in Mandarin have a very important role in achieving the level of understanding of the respondents. These results indicate that Latin numerals can be used as a new way to learn Mandarin.Keywords – Chinese Teaching Methods, Latin Numeral, Homonym.